Species composition and abundance of peat swamp fishes in selected areas of Selangor, Malaysia - Muhammad Fahmi Ahmad; Abdullah Samat (Penerbit Universiti Kebangsaan Malaysia, 2015)
A total of 22 species of freshwater fish representing 10 families were collected from peat swamp area of Kuala Langat and Sungai Dusun in Selangor. Five families, comprised of 16 species were found in Kuala Langat and 15 species belonging to 10 families in Sungai Dusun peat swamp areas. Osphronemidae was the dominant group of fishes at both areas. Higher species diversity was recorded at Sungai Dusun (H’ = 1.75) than Kuala Langat (H’ = 1.42) peat swamp. Independent t-test based on H’ values mean [t(18) = 2.764; p < 0.05] showed there are statistically difference in diversity index between areas. Species diversity was unaffected by monsoon season as precipitation occurred all year around. Dissolved oxygen is the only physical parameter measured that shows positive correlation with species diversity of fish at both areas.